2023
DOI: 10.1186/s43897-023-00073-0
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and molecular changes in peach fruit exposed to cold stress conditions

Giulia Franzoni,
Natasha Damiana Spadafora,
Tiziana Maria Sirangelo
et al.

Abstract: Storage or transportation temperature is very important for preserving the quality of fruit. However, low temperature in sensitive fruit such as peach can induce loss of quality. Fruit exposed to a specific range of temperatures and for a longer period can show chilling injury (CI) symptoms. The susceptibility to CI at low temperature varies among cultivars and genetic backgrounds. Along with agronomic management, appropriate postharvest management can limit quality losses. The importance of correct temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 130 publications
0
4
0
Order By: Relevance
“…Recent studies have shown that spraying GA 3 after harvest had a positive influence on CI in fruit during long-term storage [15]. For instance, exogenous GA 3 treatment effectively modulates the activities of many enzymes in fruit cells, alleviates chilling injury, and reduces ethylene biosynthesis, thus improving the storage quality of orchard products [16,17]. The same results were demonstrated using tomato [18], loquat [19], and green chili [20].…”
Section: Introductionmentioning
confidence: 69%
“…Recent studies have shown that spraying GA 3 after harvest had a positive influence on CI in fruit during long-term storage [15]. For instance, exogenous GA 3 treatment effectively modulates the activities of many enzymes in fruit cells, alleviates chilling injury, and reduces ethylene biosynthesis, thus improving the storage quality of orchard products [16,17]. The same results were demonstrated using tomato [18], loquat [19], and green chili [20].…”
Section: Introductionmentioning
confidence: 69%
“…Low-temperature storage is the main way of prolonging the postharvest life of fresh fruits. When exposed to temperatures lower than the optimal growth temperature, coldsensitive plants or specific plant organs may become damaged [20,22]. This study's results showed that when peach fruits were stored at about 4-5 • C, there would be severe chilling injury symptoms, such as pulp browning and flavor loss [5,23,24].…”
Section: The Levels Of Endogenous Hormones In Peach Fruits Change Wit...mentioning
confidence: 78%
“…Metabolic group, transcriptome, and other combination techniques have been widely used in many horticultural crops to reveal their response mechanism to environmental stress during growth and development or maturation and softening For example, the physiological and biochemical changes in peach fruits in the dimensions of the transcriptome, proteome, and metabolic groups during postharvest chilling injury; the molecular mechanism of peach fruit responding to low-temperature stress; and a simple and non-destructive method for the detection and evaluation of fruit chilling injury during transportation and storage can be used [20]. In addition, the integration of metabolic groups and transcriptomics laid the foundation for elucidating the molecular mechanisms of plants' responses to low-temperature stress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation